THE ROLE OF ARTIFICIAL INTELLIGENCE IN DEVELOPING MEDICAL STUDENTS’ CLINICAL REASONING SKILLS - Rahimova Fotima,; Maksudova Malika,; Nadirova Yulduz, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. The rapid development of artificial intelligence (AI) has significantly influenced medical education, particularly  in the  enhancement of clinical reasoning skills among medical students. Clinical reasoning is a core competency required for accurate  diagnosis,  effective  decision-making,  and  safe  patient  care.  This  paper explores the role of AI-driven educational technologies in supporting and enriching the learning  experience  of medical  students. AI-based tools such as intelligent tutoring systems, virtual patients, clinical decision support systems, and learning analytics are analyzed  in  terms  of  their  pedagogical  value.  The  study  highlights  the  benefits, challenges, and future prospects of integrating AI into medical curricula, emphasizing its potential to foster individualized learning, improve diagnostic accuracy, and bridge the gap between theory and clinical practice.